Oral insecticidal activity of new bacterial isolates against insects in two orders. Issue 7 (3rd July 2017) - Ruiu, Luca; Virdis, Barbara; Mura, Maria Elena; Floris, Ignazio; Satta, Alberto; Tarasco, Eustachio
ABSTRACT: According to the present research trend and legislative framework of the major world regions fostering the development and use of low-risk biocidal and plant protection products for Integrated Pest Management, the discovery of new entomopathogenic bacterial species and isolates bearing insecticidal traits against novel targets is needed in the near future. In this study, the oral insecticidal activity of bacteria isolated from septicaemic Galleria mellonella larvae was assessed against different insect pests of agricultural, forest and medical-veterinary importance, including Lepidoptera ( Lymantria dispar and Malacosoma neustria ) and Diptera ( Musca domestica and Ceratitis capitata ). This led to the identification of new entomopathogenic bacterial isolates belonging to different species including Alcaligenes aquatilis, Alcaligenes faecalis, Enterococcus mundtii, Pseudomonas protegens, Serratia nematodiphila, Serratia marcescens and Stenotrophomonas maltophilia . The majority of these isolates were toxic to gypsy moth L. dispar and, more moderately, to lackey moth M. neustria larvae. Variable degrees of virulence were observed on fly species. While the insecticidal action of some of these species was previously observed, we report for the first time the insecticidal properties of specific strains against a wider target range.